2020
DOI: 10.1521/pedi.2020.34.5.586
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Based Strategy for Interfacing Traits of the DSM-5 AMPD With Neurobiology

Abstract: The DSM-5 alternative model for personality disorders (AMPD) groups traits into domains based on factor analyses of self-report data. AMPD traits may need to be configured differently to interface with neurobiology. Focusing on biobehavioral risk for externalizing problems in 334 adults, the authors used structural modeling to evaluate how well alternative configurations of AMPD traits, operationalized using the Personality Inventory for DSM-5 (PID-5), interface with neural indicators of externalizing liabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 76 publications
(148 reference statements)
1
16
0
Order By: Relevance
“…Refining the operationalization of PID-5 Disinhibition through reference to psychophysiology pulled the construct to become a more effective bridge between report-based and neurobiological measures. Further, this new operationalization of disinhibition resulted in improved convergent and discriminant validity, more balanced factor loadings, and higher internal consistency reliability, relative to the original PID-5 disinhibition domain score (Bowyer et al, 2020). These results should not be interpreted to suggest that the internal structure of the PID-5 as originally detailed by Krueger et al (2012) is not accurate; rather, it raises questions about what criteria should be used to determine the essence of a construct.…”
Section: Why Do We Have Limited Success In Linking Units Of Analysis?mentioning
confidence: 95%
See 2 more Smart Citations
“…Refining the operationalization of PID-5 Disinhibition through reference to psychophysiology pulled the construct to become a more effective bridge between report-based and neurobiological measures. Further, this new operationalization of disinhibition resulted in improved convergent and discriminant validity, more balanced factor loadings, and higher internal consistency reliability, relative to the original PID-5 disinhibition domain score (Bowyer et al, 2020). These results should not be interpreted to suggest that the internal structure of the PID-5 as originally detailed by Krueger et al (2012) is not accurate; rather, it raises questions about what criteria should be used to determine the essence of a construct.…”
Section: Why Do We Have Limited Success In Linking Units Of Analysis?mentioning
confidence: 95%
“…Disinhibition scores show theory-consistent associations with self-report criterion variables (Al-Dajani et al, 2016; Krueger et al, 2012). In a recent study, Bowyer et al (2020) examined the latent structure of PID-5 disinhibition in a different manner: through reference to a psychophysiological factor consisting of brain responses thought to reflect cognitive control (Brennan & Baskin-Sommers, 2018; Nelson et al, 2011; Venables, Foell, et al, 2018). When including both PID-5 disinhibition and the physiological indices in a single correlated-factors model, the facet-level structure outlined in the published PID-5 no longer provided good overall fit.…”
Section: Why Do We Have Limited Success In Linking Units Of Analysis?mentioning
confidence: 99%
See 1 more Smart Citation
“…Joyner and colleagues (2021) showed that trait impulsiveness was uniquely associated with externalizing forms of psychopathology when operationalized as disinhibition, whereas impulsivity that also included negative-affectivity-related content demonstrated associations with internalizing as well as externalizing psychopathology. Along the same lines, recent research has demonstrated that it is important to consider neural referents when configuring scale-level assessments of impulsivity to more effectively reflect neurobehavioral externalizing proneness (Bowyer et al, 2020).…”
Section: Robert D Latzman: Alternative Conceptualizations Of Disposit...mentioning
confidence: 99%
“…A further important point is that concepts and measures of impulsiveness derived from dimensional models of personality are based primarily on self-report data. To the extent that such measures are considered in relation to biobehavioral systems and processes, this occurs after their operationalization in the modality of self-report (e.g., Bowyer et al, 2020; Tellegen, 1991). By contrast, developmental representations of dispositional impulsiveness—considered next—are based on the biobehavioral concept of temperament and on observations of behavioral propensities in younger-aged individuals who show evidence of heritability and stability.…”
Section: Robert D Latzman: Alternative Conceptualizations Of Disposit...mentioning
confidence: 99%